2018
DOI: 10.1080/00313831.2018.1466359
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development and Its Impact on Children in Early Childhood Education and Care: A Meta-Analysis Based on European Studies

Abstract: Short summary: This study reviews the European evidence on the impact of professional development (PD) of pre-school educators on child outcomes. A meta-analysis is used to investigate how PD of pre-school educators affects child outcomes. The studies included in the meta-analysis all concern PD in formal pre-school centers in Europe, and focus is on effects directly on child outcomes. Thus, potential effects of PD on the pre-school educators' skills, beliefs, attitudes and work conditions are not investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 32 publications
4
35
0
5
Order By: Relevance
“…Results from a meta-analysis focusing on European PD interventions point in the direction of positive short-run effects on child outcomes (Jensen and Rasmussen, 2016), i.e. confirming the positive results found in US interventions.…”
Section: Introductionsupporting
confidence: 58%
“…Results from a meta-analysis focusing on European PD interventions point in the direction of positive short-run effects on child outcomes (Jensen and Rasmussen, 2016), i.e. confirming the positive results found in US interventions.…”
Section: Introductionsupporting
confidence: 58%
“…To begin with, the notion of impact and effectiveness of CPD is still largely mysterious. There is a current lack of research and findings that shed light on which specific elements of CPD, for example, content, processes and embeddedness, that influence ECEC quality, educators’ effectiveness and child outcomes, despite there being reports of overall positive effects (Bove et al, ; Jensen & Rasmussen, ; Jensen & Iannone, ; Karwowska‐Struczyk, Wyslowska, & Wichrowsha, ). Even where research has identified certain approaches as effective (Giudici & Castagnetti, ; Jensen & Rasmussen, ; Jensen & Iannone, ), no evidence is provided on their effectiveness in relation to one another (Jensen, Iannone, Christy, & Rolls, , p. 18) and only a few studies examine communities of practice in relation to impact.…”
Section: Discussionmentioning
confidence: 99%
“…This article analyses innovative approaches to in‐service continuous professional development (CPD) in early childhood education and care (ECEC) strategies, conducted as part of the CARE Project (http://www.ecec-care.org) and published in its reports by Jensen and Iannone (), Jensen and Rasmussen (), Bove, Mantovani, Jensen, Karwowska‐Struczyk, and Wysłowska (2016) and Jensen and Iannone (). The Project's overall aim was to address the question: ‘How can the findings contribute to future policy, practice and research developments and thereby to the field by highlighting the challenges that European ECEC systems face in today's societies and how can these challenges be met through an improved professional development ECEC system?’ In this article, we focus on one part of the research that analyses the extent to which innovative approaches to ECEC systems are being developed in European countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is, then, relatively limited empirical or theoretical work, which attempts to understand the processes that support PDL in EY settings, that can bring about sustainable change in practice and impact positively on children's outcomes, despite the emphasis placed on this in a context of rapid global expansion of EY provision and an explicit focus on ‘school readiness’ (Rao et al ., ; Yoshikawa et al ., ; DfE, ). There are also challenges in identifying the efficacy of PDL programmes, not least because it is difficult to isolate the multiple variables that comprise a PDL programme to demonstrate causal links between improvements in EYE practice and outcomes for children, a point noted in two international reviews of PDL in preschool (Zaslow et al ., ; Jensen & Ranmussen, ). In the UK, specifically a number of high profile reviews of evidence on the impact and efficacy of professional learning in schools and 5–18 education have been conducted recently (see, e.g.…”
Section: Introductionmentioning
confidence: 99%